2021
DOI: 10.1371/journal.pcbi.1009250
|View full text |Cite
|
Sign up to set email alerts
|

IUSMMT: Survival mediation analysis of gene expression with multiple DNA methylation exposures and its application to cancers of TCGA

Abstract: Effective and powerful survival mediation models are currently lacking. To partly fill such knowledge gap, we particularly focus on the mediation analysis that includes multiple DNA methylations acting as exposures, one gene expression as the mediator and one survival time as the outcome. We proposed IUSMMT (intersection-union survival mixture-adjusted mediation test) to effectively examine the existence of mediation effect by fitting an empirical three-component mixture null distribution. With extensive simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 144 publications
(227 reference statements)
0
15
0
Order By: Relevance
“…Samples for this study were collected from the Manitoba IBD Cohort Study which was initiated in 2002 [ 22 ]. The genetic profiles of the same samples were used for the previous CNV and transcriptome-wide analysis [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples for this study were collected from the Manitoba IBD Cohort Study which was initiated in 2002 [ 22 ]. The genetic profiles of the same samples were used for the previous CNV and transcriptome-wide analysis [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we performed one of the first genome-wide copy number variation (CNV) analysis [ 20 ] and transcriptome-wide analysis of PC in IBD [ 21 ], which suggested that the expression level of the RBPMS gene has an association with PC status in persons with IBD [ 20 , 21 ]. Gene expression has been considered as a mediator between genetic variants and disease phenotype [ 22 ]. Hence, we hypothesized that the genetic contribution to PC susceptibility among persons with IBD could be mediated by the expression level of RBPMS .…”
Section: Introductionmentioning
confidence: 99%
“…Stool is the easiest object for analysis that can be obtained. Single‐, dual‐ and multiple‐target methylation‐specific qPCR approaches show high sensitivity (>95%) and specificity (>88%) 134,135 . Detection of circulating cell‐free methylated (ccfm) DNA in blood plasma with qPCR was shown to be highly sensitive when SEPT9 and SDC2 promoters were analyzed 75,136 .…”
Section: Sensitive Detection Of Dna Methylation In Crcmentioning
confidence: 99%
“…Single-, dual-and multiple-target methylation-specific qPCR approaches show high sensitivity (>95%) and specificity (>88%). 134,135 Detection of circulating cell-free methylated (ccfm)…”
Section: Sensitive Detection Of Dna Methylation In Crcmentioning
confidence: 99%
“…We drew a Venn plot about 1,936 genotype, 1,936 genes and 60 predictors (Figure S12), and found many common genes. Based on an explicit assumption of temporal ordering from genotype, gene expression and survival outcome, survival mediation analysis of gene expression with multiple genotype exposures is feasible, referring to (Shao, Wang et al 2021).…”
Section: Genotype and Gene Expressionmentioning
confidence: 99%